The Influence of 5′R and 5′S cdA and cdG on the Activity of BsmAI and SspI Restriction Enzymes - Szewczuk, Michał (Molecules, 2021)
Restriction endonucleases (REs) are intra-bacterial scissors that are considered tools in the fight against foreign genetic material. SspI and BsmAI, examined in this study, cleave dsDNA at their site of recognition or within a short distance of it. Both enzymes are representatives of type II REs, which have played an extremely important role in research on the genetics of organisms and molecular biology. Therefore, the study of agents affecting their activity has become highly important. Ionizing radiation may damage basic cellular mechanisms by inducing lesions in the genome, with 5′,8-cyclo-2′-deoxypurines (cdPus) as a model example. Since cdPus may become components of clustered DNA lesions (CDLs), which are unfavorable for DNA repair pathways, their impact on other cellular mechanisms is worthy of attention. This study investigated the influence of cdPus on the elements of the bacterial restriction–modification system. In this study, it was shown that cdPus present in DNA affect the activity of REs. SspI was blocked by any cdPu lesion present at the enzyme’s recognition site. When lesions were placed near the recognition sequence, the SspI was inhibited up to 46%. Moreover, (5′S)-5′,8-cyclo-2′-deoxyadenosine (ScdA) present in the oligonucleotide sequence lowered BsmAI activity more than (5′R)-5′,8-cyclo-2′-deoxyadenosine (RcdA). Interestingly, in the case of 5′,8-cyclo-2′-deoxyguanosine (cdG), both 5′S and 5′R diastereomers inhibited BsmAI activity (up to 55% more than cdA). The inhibition was weaker when cdG was present at the recognition site rather than the cleavage site.